Estudo sobre a síntese de zeólitas sodalíticas utilizando planejamento de experimentos - Sousa, Diana Nara Ribeiro de (2011)
Through the synthesis conditions used were possible to exploit different variables in order to obtain different zeolitic structures, whose main were those formed from sodalitics units (LTA and FAU). From clear solutions containing water, tetramethylammonium hydroxide, sodium hydroxide, tetraethyl orthosilicate and the aluminum isopropoxide, different combinations of these reagents in molar compositions were made and obtained zeolites with structure LTA, phase mixture LTA and FAU, FAU, GIS (NaP1). In the first design, the structure LTA pure was obtained with a high degree of crystallinity in 50% of the experiments, the other 50% were obtained materials with low crystallinity (amorphous). The most important synthesis variables to obtain the structure LTA were the content of template and crystallization temperature. In other design, the results included mixtures of phases LTA and FAU, pure FAU and GIS (NaP1) and yet many of the experiments with the presence of material with low crystallinity. Using how response the ratio between the intensities of diffraction peaks related to the LTA and FAU structures, it was observed that the most significant variables to obtain the zeolite FAU were water content, the template content, the sodium content, crystallization time and aging time. FAU structure pure can be obtained when the ratio Na2O/Al2O3 is fixed at 0.06 to particular conditions of the other variables. Thus through the statistical design of experiments could verify the synthesis variables most important for the formation of these two structures.